diffusion of buffered glutaraldehyde and formocresol from pulpotomized primary teeth - Rusmah, M.; Rahim, Z.H.A. (1992)
The diffusion of 2 percent w/v buffered glutaraldehyde and formocresol (Buckley's formula) from pulpotomized primary teeth was studied. The measurement was based on the reaction of aldehyde with Schiff's reagent. No diffusion of buffered glutaraldehyde was observed from all the glutaraldehyde-treated teeth. Traceable amounts of formocresol were, however, detected in the collecting medium of all formocresol-treated teeth as soon as 15 minutes after treatment. The amount gradually increases and peaked after 4 hours. This suggests that 2 percent w/v buffered glutaraldehyde is a better fixative with low diffusion and is biologically acceptable as a medicament in the pulpotomy of primary teeth.